2002
DOI: 10.1063/1.1512690
|View full text |Cite
|
Sign up to set email alerts
|

Model for electrical isolation of GaN by light-ion bombardment

Abstract: We present a model for electrical isolation of GaN by light-ion bombardment. In our model, a decrease in the concentration of free carriers responsible for isolation is assumed to be due to the formation of complexes of ion-beam-generated point defects with shallow donor or acceptor dopants. These defect interaction processes are described in terms of quasichemical reactions. Results show that our model can adequately describe experimental data for electrical isolation in the case of MeV light-ion irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 16 publications
2
4
0
2
Order By: Relevance
“…Such a behavior of R S may be attributed to trap charges having enough energy to escape from the traps located at the M/S interface in the semiconductor band gap. Similar results have been reported in the literature (17,(28)(29)(30)(31). Titov et al (28) showed that ion irradiation changes not only the concentration of free carriers but also the value of mobility of carriers in GaN semiconductors.…”
Section: Radiation-dependent C-v and G/w-v Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…Such a behavior of R S may be attributed to trap charges having enough energy to escape from the traps located at the M/S interface in the semiconductor band gap. Similar results have been reported in the literature (17,(28)(29)(30)(31). Titov et al (28) showed that ion irradiation changes not only the concentration of free carriers but also the value of mobility of carriers in GaN semiconductors.…”
Section: Radiation-dependent C-v and G/w-v Characteristicssupporting
confidence: 88%
“…Similar results have been reported in the literature (17,(28)(29)(30)(31). Titov et al (28) showed that ion irradiation changes not only the concentration of free carriers but also the value of mobility of carriers in GaN semiconductors. They also showed that both the carrier concentration and series resistance of the device increase with increasing doses.…”
Section: Radiation-dependent C-v and G/w-v Characteristicssupporting
confidence: 88%
“…On the other hand, with the increase in the proton energy, the intensity of PL and Raman spectra both decrease and the full width at half maximum (FWHM) of PL and Raman spectra both increase. electrical isolation in GaN has been attributed to the complexes of ion-beam-generated point defects with shallow donor or acceptor dopants [9]. The fact of the reductions in the intensity and broadening of the PL and Raman spectra are consistent with the degradation of crystallinity of the sample.…”
Section: Resultsmentioning
confidence: 88%
“…Известно, что сечение подпорогового радиационного дефектообразования на порядки величин меньше сечения захвата носителей на ловушки. Более того, захват носителей начинается только после достижения определенной критической дозы облучения [39,40,41]. К сожалению вопрос о радиационном подпороговом дефектообразовании и величине критической дозы в различных диэлектриках еще мало изучен, поэтому наши дальнейшие численные оценки носят лишь приближенный характер.…”
Section: объяснение полученных экспериментальных результатов и обосноunclassified